Keotentikan qira’at al-qur’an dan upaya pelestarian teks suci dalam lintasan sejarah - Febrian Nurzaki, Muhammad David; Safiyya, Rieke Nada; Hidayat, Hakmi (Maliki Interdisciplinary Journal, 2025)
Qira’at is a branch of Qur’anic studies that explores variations in the recitation of the Qur’an based on the narrations of different transmitters. This discipline aims to preserve the authenticity of the Qur’anic recitation as conveyed by the Prophet Muhammad (PBUH). This study examines the concept of qira’at, its historical background, transmission methods, levels, and the principles governing its system in Islam. The research employs a literature review method by analyzing various scholarly works on qira’at. The findings reveal that valid qira’at variations possess a mutawatir (mass-transmitted) chain of narration and meet three essential criteria: conformity with Arabic linguistic rules, an authentic chain of transmission, and alignment with the Uthmani script. Differences in qira’at do not compromise the authenticity of the Qur’an but rather enrich its understanding. This study concludes that qira’at is an integral part of Islamic scholarly tradition with a strong foundation and remains relevant in preserving the accuracy of Qur’anic recitation.